MODEL ANALISI PRILAKU SOSIAL EKONOMI MASYARAKAT DESA PENYANGGA DALAM PEMANFAATAN LAHAN TAMAN NASIONAL KERINCI SEBLAT DI KECAMATAN KAYU ARO BARAT: The social economic behavior analysis model of the buffer village community in land utilization of Kerinci Seblat National Park in the Kayu Aro Barat District - Fazriyas Fazriyas; Titi Elvia; Ahyauddin Ahyauddin (Jurnal Silva Tropika, 2021)
The purpose of this study to analyze the social economic model behavior in the land utilization of in the Kerinci Seblat National Park (TNKS). The sampling method in this study using the Snowball Sampling method and obtained in both villages as many as 50 respondents as the head of the family. This type of research uses quantitative and qualitative approaches. The data analysis technique in this research is multiple linear regression using primary and secondary data obtained through structured interviews (questionnaires) with farmer farmer respondents. The results of the analysis conducted show that social economic factors together have a significant effect.